MOLE AND SPREADING OF AVIAN INFLUENZA VIRUS H5N1 IN THE WORLD - E. .. Mindolina (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Over the past 45 years, more than 30 episodes of epizootic diseases among birds were described. Some of them caused human diseases, often with high mortality rate. The most crucial cases of influenza outbreaks appeared in Europe and in the USA. Avian influenza virus types of subtype H5, which are the source for the avian influenza virus subtype H5N1 presented nowadays were first isolated from a goose in 1996 and. from the deceased person in 1997 in Hong Kong. Seasonal flu outbreaks usually appear firstly in the East, and. then move to the West. Viruses, therefore, detected at early stages in Asia are analyzed and. used to predict the components, which are applicable in the vaccine preparation for the next flu season. Over the past 50 years, genetic information about constantly changing circulating influenza strains, gratuitously received through viruses data communications and. exchange between countries, and. about epidemiological tendency to infection spreading has been gathered by the wide surveillance network (Global Influenza Surveillance Network), under the guidance of WHO.